Transport of rice cyclobutane pyrimidine dimer photolyase into mitochondria relies on a targeting sequence located in its C‐terminal internal region. (31st July 2014) - Takahashi, Sayaka; Teranishi, Mika; Izumi, Masanori; Takahashi, Masaaki; Takahashi, Fumio; Hidema, Jun
Summary The cyclobutane pyrimidine dimer (CPD), which represents a major type of DNA damage induced by ultraviolet‐B (UVB) radiation, is a principal cause of UVB‐induced growth inhibition in plants. CPD photolyase is the primary enzyme for repairing CPDs and is crucial for determining the sensitivity of Oryza sativa (rice) to UVB radiation. CPD photolyase is widely distributed among species ranging from eubacteria to eukaryotes, and is classified into class I or II based on its primary structure. We previously demonstrated that rice CPD photolyase (OsPHR), which belongs to class II and is encoded by a single‐copy gene, is a unique nuclear/mitochondrial/chloroplast triple‐targeting protein; however, the location and nature of the organellar targeting information contained within OsPHR are unknown. Here, the nuclear and mitochondrial targeting signal sequences of OsPHR were identified by systematic deletion analysis. The nuclear and mitochondrial targeting sequences are harbored within residues 487–489 and 391–401 in the C‐terminal region of OsPHR (506 amino acid residues), respectively. The mitochondrial targeting signal represents a distinct topogenic sequence that differs structurally and functionally from classical N‐terminal pre‐sequences, and this region, in addition to its role in localization to the mitochondria, is essential for the proper functioning of the CPD photolyase. Furthermore, the mitochondrial targeting sequence, which is characteristic of class‐II CPD photolyases, was acquired before the divergence of class‐II CPD photolyases in eukaryotes. These results indicate that rice plants have evolved a CPD photolyase that functions in mitochondria to protect cells from the harmful effects of UVB radiation.